Asymmetric C–C Bond Formation between Chiral N‐Phosphonyl Imines and a Nickel(II)‐Complexed Glycine Schiff Base Provides Efficient Synthesis of α, β‐syn‐Diamino Acid Derivatives. Issue 22 (1st July 2013) - Sun, Hao; Zhang, Haowei; Han, Jianlin; Pan, Yi; Li, Guigen
Abstract: The group‐assisted purification asymmetric synthesis of α, β‐diamino acid derivatives was achieved by treating chiral N ‐phosphonyl imines with a Ni II ‐complexed glycine‐derived enolate; traditional purification techniques such as chromatography and recrystallization are not required. Successful control of the syn stereochemistry of the vicinal diamino products complements our previous methods that afforded anti stereoisomers; thus, all four individual isomers can be synthesized simply by changing the geometry of the enolate. In contrast to our previous synthesis in which at least 5 equiv. of the glycine Schiff base enolate was required for complete conversion, the new synthesis only needs 1.1 equiv. of the glycine Schiff base enolate to give complete diastereoselectivity (>30:1 dr ) and high yields (91–97 %). The absolute stereochemistry was unambiguously determined by X‐ray structure analysis. Abstract : α, β‐ syn ‐Diamino acid derivatives are synthesized by treating N ‐phosphonyl imines with a Ni II ‐complexed glycine‐derived enolate through group‐assisted purification (GAP) chemistry. This method does not require the use of traditional purification techniques, and the products are obtained in excellent yields with excellent diastereoselectivities (10 examples).